German pediatric intensive care transport registry: study protocol for a prospective multicenter registry - Winkler, Stefan; Dittgen, Felix; Hammond, Edmondo; Börner, Nele; Kossack, Johanna; Eifinger, Frank; van den Heuvel, Ingeborg Alijda; Klinghammer, Elias; Lieftüchter, Victoria; Paul, Pia; Perez-Ortiz, Alba; Bimboese, Patricia; et al. (Frontiers in Pediatrics, 2025)
BackgroundIn contrast to critical care transport of adults or newborns, transport of pediatric critical care patients in Germany is neither regulated by law nor centrally organized. Due to their different therapeutic needs compared to newborns or adults, critically ill children may receive insufficient treatment during transport. In some regions in Germany, pediatric centers provide specialized pediatric retrieval teams, while others organize each transport individually. Currently, no valid data on pediatric critical care transports in Germany are available, nor are they recorded in a structured manner.ObjectivesTo establish a nationwide registry for pediatric intensive care transports in Germany. The aim is to describe and analyze the need for and current practice of specialized transports. This data may be used for future demand planning.SettingTransports are documented by pediatric centers admitting pediatric patients via intensive care transports.Inclusion criteriaAll interhospital pediatric intensive care transports of children, aged >27 days and >41 + 0 weeks of corrected gestational, age to <18 years, are eligible for data entry.MethodsThe study is designed as a prospective, multicenter registry. Transport data will be collected locally at participating pediatric centers and then submitted digitally and anonymized via a secure, web-based platform.DiscussionWe anticipate high participation from pediatric intensive care units and expect to present valid data on the need for pediatric intensive care transports in Germany. This data may serve as a foundation for nationwide demand planning for pediatric intensive care transport resources.